Hubungan Kebersyukuran dan Kebahagiaan pada Lansia: Studi Moderasi Human Strength di Indonesia - Ardiansyah, Ardiansyah; Mariyani, Mariyani; Jannah, Taifatul; Juanda, Juanda (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
This study aims to determine whether gratitude is related to happiness in the elderly and whether human strength can strengthen this relationship. The background of this study is based on the importance of psychological well-being in old age, where gratitude and personal strength are believed to play a significant role in increasing happiness. The study subjects were 50 elderly people. Data were collected using the Gratitude Questionnaire (GRAT) scale by Emmons, R.A. and Tsang, J., the happiness scale using the Oxford Happiness Questionnaire (OHQ) developed by Michael Argyle and Peter Hills, and the human strength scale by Peterson. Data were analyzed using Moderated Regression Analysis. The results showed a significant relationship between gratitude and happiness, with a significance value of p = 0.000 0.005. Furthermore, the moderator variable, human strength, contributed 10.5% to strengthening this relationship. These findings indicate that psychological interventions that foster gratitude and personal strength can be an effective strategy for improving the well-being of the elderly.